Factors Influencing Banggainese Learners English Pronunciation - Mukmin; Ifandri Banet (Britain International for Academic Research (BIAR-Publisher), 2022)
The research seeks to study certain factors that obstruct the development of English pronunciation by Banggainese students. The following research questions are addressed by this research: 1. What are the factors in English pronunciation affecting Banggaini students? 2. What are the main factors affecting the English pronunciation of Banggainese learners? The participants of this research are 5 learners from Banggai Kepualauan (BangKep) who are still collaged in English Education Study Program, Muhammadiyah Luwuk University. The research design was qualitatively descriptive. The data were collected via documentation and in-depth interviews with five representatives involved in audio recording. An interview is an instrument that the researcher used as collecting data. The finding of this research is: Six factors are affecting Banggainese learners in learning English pronunciation among others are; Age of learners, language exposure, type and amount of preliminary speech instruction, skill, attitude and motivation, the role of the native language, new research directions, personal endeavors, and goals. Age of learners the result demonstrates that four dominant factors influence the pronunciation of English by Banggainese students, such as their learner age, attitude and motivation, exposure to the target language and personal efforts and the setting of goals.